Field-Induced Phase Transitions of Block Copolymers - Sun, Youhai (My University, 2007)
Block copolymers are a class of soft materials which can self-assemble into a variety of ordered structures. One method to induce new structures is the application of an external field such as an electric field. Previously, studies of the field-induced phase transitions are based on the assumption that the structural change follows certain symmetry pattern or simply using real-space numerical methods. The goal of the current project is to develop a simple analytic method to predict the structural change. Our approach is based on a linear response theory, in which the external field is taken as a perturbation and the lowest-order contribution to the solution is computed. We applied our method to the Landau-Brazovskii theory which is valid close to the order-disorder transition point of diblock copolymers. The result shows that there will be an additional term to the order parameter as a response to the external field. The structural change can be predicted by a new Fourier expansion of the order parameter. As an example, we examined the structural change of a body-centered cubic phase under an applied electric field.
Keywords: field-induced, phase transitions, block copolymers, soft materials, ordered structures, linear response theory